Acrylic copolymer resin
By adding cyclohexyl-containing comonomers into high Tg acrylic acid-based copolymers, the problems of light transmittance and water absorption in existing materials under high humidity and high temperature conditions are solved, and high light transmittance, low haze and low water absorption are achieved. effect.
Patent Information
- Application Number
- CN202380038072.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-04
- Filing Date
- 2023-03-03
- Publication Date
- 2025-02-11
AI Technical Summary
The existing high Tg acrylic copolymers are difficult to meet the requirements of high light transmittance, low haze, low water absorption and environmental stability under hot and humid conditions.
A hydrophobic high Tg-based acrylic copolymer is formed by incorporating a small amount of a high trans/cis ratio of cyclohexyl-containing comonomers into the standard methyl methacrylate (pMMA).
It achieves high light transmittance, low haze and low water absorption under high humidity and temperature conditions, while maintaining high Tg and sufficient molecular weight, suitable for complex optical and electronic applications.
Smart Images

Figure BDA0005115004910000051 
Figure BDA0005115004910000061 
Figure BDA0005115004910000321
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application is related to and claims the benefit of priority of U.S. Patent Application No. 17 / 687,222, filed on March 4, 2022, entitled Acrylic Copolymer Resins, the contents of which are incorporated herein by reference in their entirety for all purposes. Technical Field
[0003] The present invention relates to acrylic copolymers incorporating high Tg, hydrophobic (meth)acrylates and their derivatives, which have high thermal stability, especially under hot, humid conditions. Background Art
[0004] Thermoplastic polymers and copolymers, especially (meth)acrylic polymers, have characteristics such as transparency, mechanical properties and processability, and are widely used in various fields such as automobile parts, electrical parts, industrial parts, optical materials, various parts of home appliances, medical devices, signs, aesthetic parts, groceries, etc.
[0005] High Tg acrylic polymers can be used in applications requiring high optical transparency and high heat resistance, such as automotive front interior lenses, thin-walled parts, lighting tubes, optical protection / retardation films in electronic devices, solar lenses / films, household appliances, composite materials, etc. It is expected that the market for high-heat acrylic copolymers in automotive LED front interior lenses and interior thin lenses will grow rapidly. In addition, high-heat acrylic films are also used in LED / OLED displays. However, standard polymethyl methacrylate (pMMA) copolymers may lack the ability to pass strict long-term environmental stability tests (such as 80°C / 85% relative humidity (RH) and / or 85°C / 85% RH test requirements) of new optical films in automotive front interior thick lenses, automotive interior lenses, thin-walled parts / lenses, solar transparent panels / lenses, and electronic devices and smartphones. These applications generally require a combination of high glass transition temperature (Tg) and hydrophobic properties. Most high Tg monomers (such as methacrylic acid and / or maleic anhydride) are hydrophilic, and their copolymers are not moisture resistant.
[0006] High Tg acrylic copolymers, such as methyl methacrylate / methacrylic copolymers are described in US2018-0362688.
[0007] US 10,043,930 describes high Tg acrylic copolymers using various high Tg comonomers for photovoltaic cell front sheets. Summary of the invention
[0008] The present invention has demonstrated that incorporation of relatively small amounts of certain cyclohexyl-containing comonomers with high trans:cis ratios into pMMA can increase the hydrophobicity of acrylic copolymers / terpolymers while maintaining high Tg / Vicat softening temperatures and sufficiently high molecular weight for use in the aforementioned challenging market applications.
[0009] An acrylic copolymer is provided, which comprises, consists of, or essentially consists of a combination of monomers a) and monomers b) as polymerized monomers. Monomer a) comprises, consists of, or essentially consists of at least one of tert-butylcyclohexyl(meth)acrylate, 3,3,5-trimethylcyclohexyl(meth)acrylate, or a mixture thereof. The monomer is present in the acrylic copolymer at 0.2% to 20% by weight, and preferably 0.5% to 10% by weight of the monomer units in the acrylic copolymer. Monomer a) comprises, consists of, or essentially consists of at least 80% by weight, more preferably at least 85% by weight, and most preferably at least 90% by weight of the trans isomer. Monomer b) is a (meth)acrylate monomer unit, and is present in the acrylic copolymer at 80% to 99.8% by weight of the total monomer units of b). The acrylic copolymer has: i) a Tg of 116°C to 145°C, preferably 120°C to 145°C, more preferably 125°C to 145°C, and most preferably 125°C to 140°C; and ii) a weight average molecular weight (Mw) of at least 65,000 g / mol, preferably at least 75,000 g / mol, more preferably at least 90,000 g / mol, and most preferably at least 100,000 g / mol. DETAILED DESCRIPTION
[0010] "Copolymer" is used to refer to a polymer having two or more different monomer units, including copolymers and polymers having three or more different monomers, such as terpolymers and tetrapolymers. Therefore, the term "copolymer, terpolymer and tetrapolymer" covers any polymer having more than one type of comonomer. "Polymer" is used to refer to homopolymers and copolymers. The polymer may be linear, branched, star-shaped, comb-shaped, block or any other structure. The polymer may be homogeneous, heterogeneous, and may have a gradient distribution of comonomer units. All cited documents are incorporated herein by reference. As used herein, unless otherwise described, percentages shall mean weight percentages. Molecular weight is the weight average molecular weight measured by gel permeation chromatography (GPC) using polymethyl methacrylate standards. In the case where the polymer contains some crosslinking and GPC cannot be applied due to the insoluble polymer fraction, the soluble fraction / gel fraction or soluble fraction molecular weight after extraction from the gel is used to determine the weight average molecular weight.
[0011] As used herein, "hydrophobic" means that the PMMA copolymer contains at least 0.2 wt% of tert-butylcyclohexyl (meth)acrylate and / or 3,3,5-trimethylcyclohexyl (meth)acrylate hydrophobic monomer units.
[0012] As used herein, "(meth)acrylic" or "(meth)acrylate" means both acrylate and methacrylate.
[0013] In one embodiment, the hydrophobic copolymer of the present invention passes the 85°C / 85%RH test. In another embodiment, the hydrophobic copolymer of the present invention passes the -40°C to 80°C / 85%RH humidity freeze cycle test.
[0014] The present inventors have prepared copolymers that incorporate hydrophobic tert-butylcyclohexyl (meth)acrylate monomers (trans / cis isomer ratio of 80 / 20 or higher) and / or (meth)acrylate 3,3,5-trimethylcyclohexyl (meth)acrylate (trans / cis isomer ratio of 80 / 20 or higher) monomers into acrylic copolymers, terpolymers and tetrapolymers, which copolymers have sufficiently high Tg and high molecular weight to form hydrophobic, high heat resistant acrylic articles that can be used for automotive LED front thick lenses, automotive interior thin lenses, LED lighting tubes, optical films for LCD / OLED devices and smartphones, optical imaging lenses, solar transparent lenses, and other applications that require resistance to high humidity and high temperature conditions. These new hydrophobic high heat acrylic materials are designed to meet the requirements of high light transmittance in the visible light wavelength range, low haze, high heat resistance, low water / moisture absorption, environmental stability and sufficient mechanical properties, and optionally excellent UV resistance. In terms of melt processing / solution blending methods in the form of mixtures (blends) and / or combinations, hydrophobic high Tg copolymers or terpolymers (refractive index of 1.47-1.50) are physically compatible with selected polymers and optical acrylic copolymers. The weight percentage of the hydrophobic high heat copolymers (containing tert-butyl cyclohexyl methacrylate) used in homopolymer and copolymer blends can be in the range of 10% to 90% by weight of the total composition. The optical protection optical properties of these copolymers or their compositions have a transmittance higher than 91%, less than 2%, preferably less than 0.5% optical haze. The copolymers and their blends have high Tg, excellent thermal stability, low water absorption / moisture absorption, excellent mechanical properties and excellent environmental stability, as demonstrated by -40°C to 80°C / 85% RH humidity freezing cycles and / or 85°C / 85% RH test protocols.
[0015] Highly heat resistant pMMA materials containing hydrophobic tert-butylcyclohexyl methacrylate and / or 3,3,5-trimethylcyclohexyl (meth)acrylate can have and / or be characterized by high heat resistance, high light transmittance, low haze, low water / moisture absorption, environmental stability. These materials also have excellent mechanical properties and excellent UV resistance.
[0016] These optical grade resins can be prepared by processes such as, but not limited to, melt polymerization, solution polymerization, emulsion polymerization, and suspension polymerization.
[0017] Optical films and / or sheets made of, comprising, consisting of, or consisting essentially of the copolymers of the present invention may have a light transmittance greater than 91% and / or an optical haze less than 2.5%.
[0018] The present invention relates to the structure-property relationship of optically hydrophobic high heat resistant acrylic copolymers / terpolymers, which can be used for thick front inner lenses of automotive LEDs, thin lenses for automotive interiors, automotive LED lighting tubes, optical protection / retardation films in LCD / OLED electronic devices, solar transparent panels / lenses, household appliances (e.g., dishwashers), medical devices, composite materials and other applications. In addition, these high heat resistant pMMA copolymers are also used for thin-walled parts, such as external optical lenses and dashboards. If energy-saving OLED technology is widely used, the area of optical polarizing films for OLEDs will increase, depending on the capacity. Other applications can include digital printing of signs, film in-mold decoration, surface protection films, medical devices, lithium-ion battery adhesives, window profiles and even co-extrusion applications.
[0019] tert-Butyl cyclohexyl methacrylate
[0020] The structural formula of tert-butyl cyclohexyl (meth)acrylate is as follows:
[0021]
[0022] Monomer (meth) tert-butyl cyclohexyl acrylate is a mixture of cis-form and trans-form about cyclohexyl group. It has been unexpectedly found that the ratio of cis-isomer and trans-isomer has an impact on the heat resistance and moisture resistance of the resulting multipolymer. In order to provide high Tg multipolymer, tert-butyl cyclohexyl (meth) acrylate monomer comprises at least 80 wt %, more preferably at least 85 wt %, and most preferably at least 90 wt % trans-isomer, is composed of it, or is basically composed of it. Tert-butyl cyclohexyl (meth) acrylate can comprise at least 81 wt %, 82 wt %, 83 wt %, 84 wt %, 86 wt %, 87 wt %, 88 wt %, 89 wt %, 91 wt %, 92 wt %, 93 wt %, 94 wt %, 95 wt %, 96 wt % or 97 wt % trans-isomer by the weight of tert-butyl cyclohexyl (meth) acrylate monomer, is composed of it, or is basically composed of it.
[0023] The level of tert-butylcyclohexyl (meth)acrylate in the final copolymer may range from 0.2 wt% to 20 wt% based on the weight of the copolymer, and more preferably 0.5 wt% to 10 wt% of tert-butylcyclohexyl (meth)acrylate in the copolymer. It has been found that as little as 1 wt%, and even 0.5 wt% of tert-butylcyclohexyl (meth)acrylate, can provide a copolymer having hydrophobic properties while also providing a sufficiently high Tg to pass rigorous high humidity, high heat testing protocols. For example, such copolymers may comprise 0.2% to 15% by weight, 0.3% to 15% by weight, 0.4% to 10% by weight, 0.5% to 9% by weight, 0.6% to 8% by weight, 0.7% to 7% by weight, 0.8% to 6% by weight, 0.9% to 5% by weight, 1% to 5% by weight, 1% to 6% by weight, 1% to 7% by weight, 1% to 8% by weight, 1% to 10% by weight, 3% to 10% by weight, 1% to 30% by weight, 1% to 15% by weight, 1% to 1 ... , 5% to 20% by weight, 5% to 15% by weight, 10% to 15% by weight, 10% to 20% by weight, 5% to 10% by weight, 0.2% to 10% by weight, 0.2% to 15% by weight, 0.2% to 8% by weight, 0.2% to 5% by weight, 0.5% to 15% by weight, 1% to 10% by weight, 1% to 5% by weight, 10% to 15% by weight or 5% to 15% by weight of tert-butyl cyclohexyl (meth)acrylate.
[0024] 3,3,5-Trimethylcyclohexyl (meth)acrylate
[0025] 3,3,5-Trimethylcyclohexyl (meth)acrylate is a mixture of cis-form and trans-form (with respect to the cyclohexyl group) and has the following structural formula:
[0026]
[0027] The monomer 3,3,5-trimethylcyclohexyl (meth)acrylate is a mixture of cis- and trans-forms with respect to the cyclohexyl group. It has been unexpectedly found that the ratio of cis- to trans-isomers has an effect on the heat and moisture resistance of the resulting copolymer. In order to provide a high Tg copolymer, 3,3,5-trimethylcyclohexyl (meth)acrylate comprises, consists of, or consists essentially of at least 80% by weight, more preferably at least 85% by weight, and most preferably at least 90% by weight of the trans-isomer. The 3,3,5-trimethylcyclohexyl (meth)acrylate monomer can comprise, consist of, or consist essentially of at least 81, 82, 83, 84, 86, 87, 88, 89, 91, 92, 93, 94, 95, 96, or 97% by weight of the trans isomer, based on the weight of the 3,3,5-trimethylcyclohexyl (meth)acrylate monomer.
[0028] The level of 3,3,5-trimethylcyclohexyl (meth)acrylate in the final copolymer is typically in the range of 0.2% to 20% by weight, and more preferably 0.5% to 10% by weight of the 3,3,5-trimethylcyclohexyl (meth)acrylate used in the copolymer. It has been found that as little as 1% by weight, and even 0.5% by weight of 3,3,5-trimethylcyclohexyl (meth)acrylate monomer can provide a copolymer having hydrophobic properties while also providing a high enough Tg to pass rigorous high humidity, high heat testing protocols. For example, such copolymers may comprise 0.2% to 15% by weight, 0.3% to 15% by weight, 0.4% to 10% by weight, 0.5% to 9% by weight, 0.6% to 8% by weight, 0.7% to 7% by weight, 0.8% to 6% by weight, 0.9% to 5% by weight, 1% to 5% by weight, 1% to 6% by weight, 1% to 7% by weight, 1% to 8% by weight, 1% to 10% by weight, 3% to 5% by weight, 1% to 15% by weight, 1% to 20% by weight, 1% to 30% by weight, 1% to 50% by weight, 1% to 100% by weight, 1% to 20% by weight, 1% to 30% by weight, 1% to 5 ... % to 20 wt %, 5 wt % to 15 wt %, 10 wt % to 15 wt %, 10 wt % to 20 wt %, 5 wt % to 10 wt %, 0.2 wt % to 10 wt %, 0.2 wt % to 15 wt %, 0.2 wt % to 8 wt %, 0.2 wt % to 5 wt %, 0.5 wt % to 15 wt %, 1 wt % to 10 wt %, 1 wt % to 5 wt %, 10 wt % to 15 wt %, or 5 wt % to 15 wt % of 3,3,5-trimethylcyclohexyl (meth)acrylate monomer.
[0029] A blend of 3,3,5-trimethylcyclohexyl (meth)acrylate monomer and tert-butylcyclohexyl (meth)acrylate can be used to form the copolymer of the present invention. The monomer blend can comprise, consist of, or consist essentially of 1 to 100 weight percent of 3,3,5-trimethylcyclohexyl (meth)acrylate monomer and 100 to 1 weight percent of tert-butylcyclohexyl (meth)acrylate.
[0030] To provide a high Tg copolymer, the blend of these monomers comprises, consists of, or consists essentially of at least 80 wt %, more preferably at least 85 wt %, and most preferably at least 90 wt % trans isomer. The monomer blend may comprise, consist of, or consists essentially of at least 81 wt %, 82 wt %, 83 wt %, 84 wt %, 86 wt %, 87 wt %, 88 wt %, 89 wt %, 91 wt %, 92 wt %, 93 wt %, 94 wt %, 95 wt %, 96 wt %, or 97 wt % trans isomer, based on the weight of the monomer blend.
[0031] The level of the blend of monomers in the final copolymer is generally in the range of 0.2% to 20% by weight of the monomer blend that may be present in the copolymer, and more preferably 0.5% to 10% by weight. It has been found that only 1% by weight, and even 0.5% by weight of the monomer mixture, can provide a copolymer with hydrophobic properties while also providing a sufficiently high Tg to pass rigorous high humidity, high heat testing protocols. For example, such copolymers may include 0.2% to 15% by weight, 0.3% to 15% by weight, 0.4% to 10% by weight, 0.5% to 9% by weight, 0.6% to 8% by weight, 0.7% to 7% by weight, 0.8% to 6% by weight, 0.9% to 5% by weight, 1% to 5% by weight, 1.5% to 5% by weight, 1% to 6% by weight, 1% to 7% by weight, 1% to 8% by weight, 1% to 10% by weight, % to 10 wt%, 5 wt% to 20 wt%, 5 wt% to 15 wt%, 10 wt% to 15 wt%, 10 wt% to 20 wt%, 5 wt% to 10 wt%, 0.2 wt% to 10 wt%, 0.2 wt% to 15 wt%, 0.2 wt% to 8 wt%, 0.2 wt% to 5 wt%, 0.5 wt% to 15 wt%, 1 wt% to 10 wt%, 1 wt% to 5 wt%, 10 wt% to 15 wt%, or 5 wt% to 15 wt% of a monomer blend.
[0032] According to one embodiment, the copolymer comprising trimethylcyclohexyl (meth)acrylate and / or tert-butylcyclohexyl (meth)acrylate may have a syndiotacticity (rr) of at least 50%, more preferably at least 55%, and most preferably at least 60% of the copolymer, as measured by the method described in the examples. The syndiotacticity (rr) of the copolymer may be at least 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% or 80%.
[0033] The copolymers, terpolymers or tetrapolymers of the present invention can have a refractive index of 1.47 to 1.50 at a wavelength of 589 nm. These materials can also have a haze value of less than 2.5%, more preferably less than 1.5% and most preferably less than 0.5%. The haze value of the copolymer can be less than 2.4%, 2.3%, 2.2%, 2.1%, 2.0%, 1.9%, 1.8%, 1.7%, 1.6%, 1.4%, 1.3%, 1.2%, 1.1%, 1.0%, 0.9%, 0.8%, 0.8%, 0.6%, 0.4%, 0.3% or 0.2%, as measured using the method described in the Examples.
[0034] The copolymer, terpolymer or tetrapolymer may have a transmittance value of at least 91%, more preferably at least 91.5% and most preferably at least 92% at a wavelength of 560 nm through a 120 μm film. The copolymer, terpolymer or tetrapolymer may have a refractive index of 1.47 to 1.50 at a wavelength of 589 nm. The copolymer, terpolymer or tetrapolymer may have a water absorption of less than 2% by weight, preferably less than 1.5% by weight and most preferably less than 1.3% by weight after being placed in water at 60° C. for at least 504 hours. The water absorption may be less than 1.9%, 1.8%, 1.7%, 1.6%, 1.4%, 1.3%, 1.2%, 1.1% by weight or less than 1% by weight after being placed in water at 60° C. for at least 504 hours. According to one embodiment, a 3.2 mm thick sample of the copolymer, terpolymer, or tetrapolymer may have no visible stress cracks or cracking defects after exposure to 75 cycles of -40°C to 80°C / 85% RH for 600 hours.
[0035] Acrylic monomer, methyl methacrylate (MMA)
[0036] One or more hydrophobic high Tg monomers are copolymerized with one or more other monomers. In a preferred embodiment of the present invention, the copolymer contains at least 50% by weight of methyl methacrylate monomer units constituting the copolymer, preferably at least 70% by weight and more preferably at least 80% by weight of methyl methacrylate monomer units constituting the copolymer. According to one embodiment, the acrylic copolymer comprises, consists of, or essentially consists of 80% to 99.8% by weight of (meth)acrylate monomer units based on the total weight of the copolymer. The copolymer of the present invention may comprise, consist of, or essentially consists of at least 51% by weight of methyl methacrylate monomer units. %, 73 wt %, 74 wt %, 75 wt %, 76 wt %, 77 wt %, 79 wt %, 81 wt %, 82 wt %, 83 wt %, 84 wt %, 85 wt %, 86 wt %, 87 wt %, 88 wt %, 89 wt %, 90 wt %, 91 wt %, 92 wt %, 93 wt %, 94 wt %, 95 wt %, 96 wt %, 97 wt %, 98 wt %, 99 wt %, 100 wt %, 101 wt %, 102 wt %, 103 wt %, 104 wt %, 105 wt %, 106 wt %, 107 wt %, 108 wt %, 109 wt %, 110 %, consist of, or consist essentially of 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 98.5, 98.6, 98.7, 98.9, 99, 99.1, 99.2, 99.3, 99.4, 99.5, 99.6, 99.7 or 99.8% by weight of methyl methacrylate monomer units.
[0037] The copolymers of the present invention may also include, consist of, or consist essentially of 0% to 49.5% by weight of other acrylate and methacrylate monomers or other ethylenically unsaturated monomers (including, but not limited to, styrene, alpha methyl styrene, acrylonitrile, and derivatives thereof) in addition to the hydrophobic, high Tg monomers and methyl methacrylate. A low level of crosslinking agent may also be present in the monomer mixture. Suitable acrylate and methacrylate comonomers include, but are not limited to, methyl acrylate, ethyl acrylate and ethyl methacrylate, butyl acrylate and butyl methacrylate, isooctyl methacrylate and isooctyl methacrylate, lauryl acrylate and lauryl methacrylate, octadecyl acrylate and octadecyl methacrylate, isobornyl acrylate and isobornyl methacrylate, methoxyethyl acrylate and methoxymethylacrylate, 2-ethoxyethyl acrylate and 2-ethoxyethyl methacrylate, and dimethylaminoethyl acrylate and dimethylaminoethyl methacrylate monomers. (Meth)acrylic acids such as methacrylic acid and acrylic acid may be used in the monomer mixture. In addition to carboxyl functional groups, other functional groups may be added to the copolymer by incorporating functional comonomers including epoxy (such as glycidyl methacrylate), hydroxyl and anhydride functional groups. Functional monomer units (monomer units having functional groups) may be present in up to 70 wt %, preferably up to 50 wt % of the copolymer of the present invention.
[0038] According to one embodiment, the copolymer may include, consist of, or consist essentially of other comonomers copolymerizable with hydrophobic comonomers tert-butyl cyclohexyl methacrylate and / or (meth) acrylic acid 3,3,5-trimethylcyclohexyl and (meth) acrylic acid ester monomer units. The other comonomers may be present in the polymer at 0.01 wt % to 49.9 wt %. The comonomer may be present in the form of polymerized monomers at 0.01 wt % to 25 wt %, preferably 1 wt % to 10 wt %, and most preferably 2 wt % to 5 wt %, based on the weight of the acrylic copolymer. The comonomer may be methacrylic acid, acrylic acid, itaconic acid, alpha methylstyrene, maleic anhydride, maleimide, isobornyl methacrylate, norbornyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, tetrahydrofuran methacrylate, acrylamide and methacrylamide, and at least one of their mixtures.
[0039] In addition to tert-butyl cyclohexyl methacrylate and 3,3,5-trimethylcyclohexyl (meth)acrylate, other high Tg monomers may optionally be present at levels of 0 wt % to 25 wt % and more preferably 0 wt % to 10 wt %. The other high Tg monomers may be hydrophilic, hydrophobic or neutral in character and include, but are not limited to, methacrylic acid, acrylic acid, itaconic acid, alpha methylstyrene, maleic anhydride, maleimide, isobornyl methacrylate, norbornyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, acrylamide and methacrylamide.
[0040] In one embodiment, the hydrophobic effect of tert-butylcyclohexyl methacrylate and / or 3,3,5-trimethylcyclohexyl (meth)acrylate was found to be strong enough to overcome the hydrophilic effect of the hydrophilic comonomer used at lower levels, resulting in an overall hydrophobic copolymer.
[0041] Synthesis process
[0042] The copolymer of the present invention is obtained by melt polymerization (including but not limited to solution polymerization, emulsion polymerization and suspension polymerization).
[0043] additive
[0044] The copolymers of the present invention can be blended with typical additives used in thermoplastics, including but not limited to fillers, surface modification additives, processing aids, fibers, lubricants, matting agents, heat stabilizers, flame retardants, synergists, pigments or colorants.
[0045] Other polymer additives may include polycarbonates, polyurethanes, polysulfones, polyamides, polyolefins, including copolymers and terpolymers based on these polymers, and including linear, branched, block and grafted polymer structures. Examples of matting agents include, but are not limited to, cross-linked polymer particles of various geometric shapes. The amount of fillers and additives included in the polymer composition of each layer may vary from about 0.01% to about 70% of the combined weight of polymer, additives and fillers. Typically, amounts of about 5% to about 45%, about 10% to about 40% are included.
[0046] Impact modifier
[0047] Impact modifier can be incorporated into the copolymer of the present invention or its blend together with other polymers. Suitable impact modifier can include core-shell impact modifier, consist of it, or consist essentially of it. In addition, acrylic impact modifier (such as MPD91 or MPD85T, from Altuglas, and small impact modifier-SIM) can be added to the copolymer of the present invention or the composition comprising the copolymer of the present invention, to provide the impact pMMA resin with hydrophobicity and high thermal performance, thereby improving water resistance and high heat resistance. The impact-modified composition can include 5 wt % to 60 wt %, preferably 5 wt % to 50 wt %, more preferably 20 wt % to 50 wt % of the impact modifier based on the total weight of the composition comprising impact modifier and copolymer of the present invention. Impact modifier can include core-shell impact modifier, acrylic block copolymer or self-assembled nanostructure polymer, or at least one of any combination thereof, consist of it or consist essentially of it.
[0048] Blends with other polymers
[0049] Other polymers can be blended with the copolymers of the present invention. For example, poly(methyl (meth)acrylate) / ethyl (meth)acrylate copolymers; poly(methyl methacrylate) / methacrylate copolymers, poly(styrene acrylonitrile, SAN), polyvinylidene fluoride, copolymers of vinylidene fluoride and hexafluoropropylene; polylactic acid; and combinations thereof can be blended with the copolymers of the present invention to provide polymer compositions. Advantageously, the hydrophobic high heat resistant pMMA copolymers / terpolymers of the present invention can be blended with Block copolymers (from Arkema), styrene acrylonitrile copolymers (SAN), polyvinylidene fluoride (PVDF) homopolymers, poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) copolymers and other compatible polymers are blended for different applications, such as but not limited to coextruded profiles for architectural applications, household appliances (such as parts in dishwashers), film laminates for reflective signage. The present invention also contemplates blends of the copolymers of the present invention with other polymers, especially acrylic polymers. In terms of melt processing / solution blending in mixtures and / or combinations, the copolymers of the present invention or the terpolymers of the present invention (refractive index of 1.47-1.50) are optically and physically compatible with many typical optical acrylic copolymers (refractive index of about 1.49). The copolymers of the present invention are typically blended with other acrylic resins at 5% to 95% by weight, preferably 5% to 75% by weight and more preferably 10% to 60% by weight of the total polymer solids.
[0050] Blends with other compatible polymers in various ratios are also contemplated. Compatible polymers particularly useful for blends include, but are not limited to, other poly(methyl methacrylate) copolymers, such as polymethyl methacrylate-ethyl acrylate (pMMA-EA) and polymethyl methacrylate-methyl acrylate (PMMA-MA), poly(styrene-acrylonitrile, SAN), polyvinylidene fluoride, copolymers of vinylidene fluoride and hexafluoropropylene, and polylactic acid.
[0051] Antioxidants
[0052] In one embodiment, selected antioxidants can be used to improve the thermal stability of the resin at high temperatures (such as 255°C-275°C) and reduce yellowing at high temperatures. The loading of the antioxidant in the final resin formulation is at a level of about 50ppm to 3500ppm, preferably about 100ppm to about 2500ppm based on the total weight of the composition. Non-limiting examples of useful antioxidants include sterically hindered phenolic compounds, organic phosphites, hindered amine light stabilizers (HALS), benzotriazoles, triazines, benzophenones, and cyanoacrylates. For example, the copolymer may include 100 to 2000ppm by weight or 2500ppm by weight of an antioxidant, which includes at least one of hydroxyphenylbenzotriazole, sterically hindered phenolic compounds, organic phosphites, hindered amines, and combinations thereof. These antioxidants are used to improve the thermal stability of the resin at high temperatures such as 255°C to 275°C and reduce yellowing at high temperatures. The loading level of antioxidant in the final resin formulation ranges from 100 ppm to 2000 ppm by weight, or from 150 ppm to 1900 ppm, or from 200 ppm to 1800 ppm, or from 150 ppm to 1500 ppm, or from 100 ppm to 1000 ppm by weight.
[0053] characteristic
[0054] The novel hydrophobic high heat acrylic materials of the present invention are designed to meet the requirements of high light transmittance in the visible wavelength range, low haze, high heat resistance, low water / moisture absorption, environmental stability and sufficient mechanical properties, and optionally excellent UV resistance, making them particularly suitable for certain high heat, high optical clarity applications. These properties are achieved by the copolymer itself or a composition containing the copolymer of the present invention, the composition comprising additives, impact modifiers, antioxidants and additional polymers as described above.
[0055] The polymer composition may have a haze value of less than 2.5%, more preferably less than 1.5% and most preferably less than 0.5%. The polymer composition may have a transmittance value of at least 91%, more preferably at least 91.5% and most preferably at least 92% through a 120 μm film at a wavelength of 560 nm. The polymer composition may have a refractive index of 1.47 to 1.50 at a wavelength of 589 nm. The polymer composition may have a water absorption of less than 2% by weight, preferably less than 1.5% by weight and most preferably less than 1.3% by weight after being placed in water at 60° C. for at least 504 hours. According to one embodiment, a 3.2 mm thick sample of a polymer composition comprising a copolymer of the present invention may have no visible stress cracks or cracking defects after being exposed to 75 cycles of -40° C. to 80° C. / 85% RH for 600 hours.
[0056] The Tg of the copolymer is generally in the range of 115°C to 150°C, preferably 116°C to 140°C and more preferably 120°C to 130°C. The Tg value of the acrylic copolymer is greater than 116°C, preferably greater than 120°C, more preferably greater than 125°C and more preferably greater than 130°C. The Tg of the copolymer may be 116°C to 145°C, preferably 120°C to 145°C, more preferably 125°C to 145°C and most preferably 125°C to 140°C. The Tg of the copolymer may be 130°C to 145°C, or 130°C to 140°C. The Tg of the copolymer may be greater than 117° C., 118° C., 119° C., 121° C., 122° C., 123° C., 124° C., 125° C., 126° C., 127° C., 128° C., 129° C., 131° C., 132° C., 133° C., 134° C., 135° C., 136° C., 137° C., 138° C., or 139° C. In a preferred embodiment, the acrylic copolymer has a high Tg of greater than 115° C., more preferably greater than 120° C., greater than 125° C., greater than 130° C., greater than 135° C., and even greater than 140° C. The Tg of the copolymer may be greater than 141° C., 142° C., 143° C., 144° C., 145° C., 146° C., 147° C., 148° C., 149° C., or 150° C.
[0057] The weight average molecular weight of the acrylic copolymer is greater than 65,000 g / mol, preferably greater than 75,000 g / mol, more preferably greater than 90,000 g / mol and even more preferably greater than 100,000 g / mol. The maximum molecular weight is about 250,000 g / mol and more preferably about 200,000 g / mol. The weight average molecular weight of these hydrophobic pMMA copolymers is greater than 65,000 g / mol, preferably greater than 75,000 g / mol, more preferably greater than 90,000 g / mol and more preferably greater than 100,000 g / mol. The weight average molecular weight of these copolymers can be greater than 70,000 g / mol, 75,000 g / mol, 80,000 g / mol, 90,000 g / mol, 100,000 g / mol, 110,000 g / mol, 120,000 g / mol, 130,000 g / mol, 140,000 g / mol, 150,000 g / mol, 160,000 g / mol, 170,000 g / mol, 180,000 g / mol, 190,000 g / mol and / or 200,000 g / mol.
[0058] The hydrophobic high Tg copolymers of the present invention, including copolymers, terpolymers and tetrapolymers of the present invention, have a refractive index of 1.47-1.50 at a wavelength of 589 nm. The copolymers of the present invention have excellent optical properties, a total white light transmittance (TWLT) of at least 89%, preferably at least 91% and more preferably at least 92%; an optical haze of less than 5%, preferably less than 3% and most preferably less than 2%.
[0059] In addition to the above-mentioned properties, the copolymer of the present invention also has excellent environmental stability, excellent mechanical properties, and excellent UV resistance.
[0060] application
[0061] The copolymer of the present invention has thermoplasticity and can be easily formed into sheets, films, lighting tubes and lenses.
[0062] Excellent thermal stability, high molecular weight, moisture resistance and excellent optical properties make the copolymers of the present invention particularly suitable for forming lighting tubes, thin-walled parts, optical lenses, extruded films, (co)extruded sheets / profiles, thermoformed sheets, cast sheets, composite materials, etc.
[0063] The high heat-resistant acrylic film of the present invention can be used in LED / OLED displays. If energy-saving OLED technology is widely used to replace LED / LCD technology, the number of new thin polarizers for OLED can be increased, while the number of traditional polarizers for LCD will be reduced.
[0064] The copolymer and the composition comprising the copolymer can form or be used as part of an article, such as a thick front inner lens of an automobile, a thin lens of an automobile, a smartphone, an imaging lens, a photovoltaic cell, a high heat LED diffuser sheet / film, a digital print of a hydrophobic surface, a (window) profile, a protective surface application, a thin wall automobile part, an electronic component, an optical thin polarizer for LED / OLED display, a notebook computer, and an electronic component in a solar electronic device (lens / panel / backplane). Other such articles in which the copolymer of the present invention can be used are at least one of a thick front inner lens of an automobile, a thin lens of an automobile, a smartphone, an imaging lens, a photovoltaic cell, a high heat LED diffuser sheet / film, a digital print of a hydrophobic surface, a (window) profile, a surface protection application, a medical device, a lithium ion battery adhesive, a thin wall automobile part, an electronic component, an optical thin polarizer for LED / OLED display, a notebook computer, and an electronic component in a solar electronic device (lens / panel / backplane).
[0065] In this specification, the embodiments have been described in a manner that enables a clear and concise description to be written, but it is intended and should be understood that the embodiments can be variously combined or separated without departing from the present invention. For example, it should be understood that all preferred features described herein are applicable to all aspects of the present invention described herein.
[0066] Non-limiting aspects of the invention are summarized below.
[0067] Aspect 1: An acrylic copolymer comprising as a polymerizable monomer:
[0068] a) 0.2 to 20 wt. %, preferably 0.5 to 10 wt. % of monomer units comprising at least one of tert-butylcyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate or a mixture thereof; wherein the monomer a) comprises at least 80 wt. %, more preferably at least 85 wt. % and most preferably at least 90 wt. % of the trans isomer;
[0069] b) 80% to 99.8% by weight of (meth)acrylate monomer units;
[0070] The acrylic copolymer has:
[0071] i) a Tg of 116°C to 145°C, preferably 120°C to 145°C, more preferably 125°C to 145°C and most preferably 125°C to 140°C; and
[0072] ii) a weight average molecular weight (Mw) of at least 65,000 g / mol, preferably at least 75,000 g / mol, and more preferably at least 90,000 g / mol and most preferably at least 100,000 g / mol.
[0073] 2: The acrylic copolymer according to aspect 1, wherein the acrylic copolymer has:
[0074] iii) a syndiotacticity (rr) of at least 50%, more preferably at least 55% and most preferably at least 60%.
[0075] Aspect 3: The acrylic copolymer according to aspect 1 or aspect 2, wherein the acrylic copolymer has the following characteristics:
[0076] iv) a haze value of less than 2.5%, more preferably less than 1.5% and most preferably less than 0.5%;
[0077] v) a light transmittance value through a 120 μm film at a wavelength of 560 nm of at least 91%, more preferably at least 91.5% and most preferably at least 92%;
[0078] vi) a refractive index of 1.47 to 1.50 at a wavelength of 589 nm; and
[0079] vii) a water absorption of less than 2 wt%, preferably less than 1.5 wt% and most preferably less than 1.3 wt% after being placed in water at 60°C for at least 504 hours.
[0080] Aspect 4: The acrylic copolymer of any one of aspects 1 to 3, wherein the copolymer comprises at least 51 wt% of methyl methacrylate monomer units.
[0081] Aspect 5: The acrylic copolymer according to any one of Aspects 1 to 4, further comprising as a polymerized monomer:
[0082] c) 0.01% to 49.9% by weight of at least one additional monomer copolymerizable with monomer a) and monomer b).
[0083] Aspect 6: The acrylic copolymer as described in Aspect 5, wherein the additional monomer c) includes at least one of methacrylic acid, acrylic acid, itaconic acid, α-methylstyrene, maleic anhydride, maleimide, isobornyl methacrylate, norbornyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, tetrahydrofuranyl methacrylate, acrylamide and methacrylamide, and mixtures thereof.
[0084] Aspect 7: The acrylic copolymer of aspect 5 or aspect 6, wherein the monomer c) is present in the form of polymerized monomers at 0.01 wt % to 25 wt %, preferably 1 wt % to 10 wt %, and most preferably 2 wt % to 5 wt %, based on the weight of the acrylic copolymer.
[0085] Aspect 8: A composition comprising the acrylic copolymer according to any one of aspects 1 to 7.
[0086] Aspect 9: The composition as described in Aspect 8, comprising 100 ppm to 2000 ppm by weight of an antioxidant, wherein the antioxidant comprises at least one of hydroxyphenylbenzotriazole, a sterically hindered phenolic compound, an organic phosphite, a hindered amine, and a combination thereof.
[0087] Aspect 10: The composition of aspect 8 or aspect 9, comprising 5 wt% to 60 wt%, preferably 5 wt% to 50 wt%, more preferably 20 wt% to 50 wt% of the impact modifier based on the total weight of the composition.
[0088] Aspect 11: The composition of aspect 10, wherein the impact modifier comprises at least one of a core-shell impact modifier, an acrylic block copolymer, or a self-assembled nanostructured polymer, or any combination thereof.
[0089] Aspect 12: The composition of aspect 10 or aspect 11, wherein the impact modifier comprises a core-shell impact modifier.
[0090] Aspect 13: A composition as described in any of Aspects 8 to 12, comprising at least one of poly(methyl methacrylate) / ethyl acrylate copolymer; poly(methyl methacrylate) / methyl acrylate copolymer; poly(methyl methacrylate) / methacrylate copolymer; poly(styrene acrylonitrile, SAN); polyvinylidene fluoride; a copolymer of vinylidene fluoride and hexafluoropropylene; polylactic acid; or a combination thereof.
[0091] Aspect 14: A composition as described in any of Aspects 8 to 13, wherein the composition comprises an effective amount of one or more additives, the additives including at least one of an impact modifier, a filler, a surface modification additive, a processing aid, a fiber, a lubricant, a matting agent, a thermal stabilizer, a flame retardant, a synergist, a pigment or a colorant.
[0092] Aspect 15: The composition according to any one of aspects 8 to 14, wherein the composition has the following characteristics:
[0093] iv) a haze value of less than 2.5%, more preferably less than 1.5% and most preferably less than 0.5%;
[0094] v) a light transmittance value through a 120 μm film at a wavelength of 560 nm of at least 91%, more preferably at least 91.5% and most preferably at least 92%;
[0095] vi) a refractive index of 1.47 to 1.50 at a wavelength of 589 nm; and
[0096] vii) a water absorption of less than 2 wt%, preferably less than 1.5 wt% and most preferably less than 1.3 wt% after being placed in water at 60°C for at least 504 hours.
[0097] Aspect 16: The composition of any of Aspects 8 to 15, wherein a 3.2 mm thick sample of the composition has no visible stress cracks or cracking defects after exposure to 75 cycles of -40°C to 80°C / 85% RH for 600 hours.
[0098] Aspect 17: An article comprising an acrylic copolymer as described in any one of Aspects 1 to 7, wherein the article is at least one of an automotive front interior thick lens, an automotive interior thin lens, a smart phone, an imaging lens, a photovoltaic cell, a high heat LED diffuser sheet / film, a digital print with a hydrophobic surface, a (window) profile, surface protection, an application, an automotive thin-walled part, a medical device, a lithium-ion battery adhesive, an electronic component, an optically thin polarizer for LED / OLED displays, a laptop computer, and an electronic component in a solar electronic device (lens / panel / backplane).
[0099] Aspect 18: An article comprising a composition as described in any of Aspects 8 to 16, wherein the article is at least one of an automotive front interior thick lens, an automotive thin lens, a smart phone, an imaging lens, a photovoltaic cell, a high heat LED diffuser sheet / film, a digital print with a hydrophobic surface, a (window) profile, a weather-resistant reinforced resin (capstock) application, an automotive thin-walled part, an electronic component, an optically thin polarizer for LED / OLED displays, a laptop computer, and an electronic component in a solar electronic device (lens / panel / backplane).
[0100] Example
[0101] Test Method :
[0102] Injection molding samples : In the following tests involving injection molded samples or plaques, the plaque sample dimensions were molded as 45 mm (width) x 67 mm (length) x 3.2 mm (thickness).
[0103] Melt Flow Rate (MFR) MeasurementThe melt flow rate of the polymer was measured using an Instron Ceast MF30 device. The mold temperature was controlled at 230°C and the load cell weight was 3.8 kg. The dried pellets were heated below T g Use within 8 hours at a temperature close to 20°C.
[0104] Gel Permeation Chromatography (GPC): Polymer molecular weight measurements were performed using a Waters Alliance 2695 and a Waters DifferentialRefractometer 2410. The columns were based on two PL Gel mixed C columns and a guard column (7.8 mm ID x 30 cm, 5 μm). THF (HPLC grade) was selected as the solvent. The temperature was controlled at 35°C. Ten poly(methyl methacrylate) standards were used in the calibration, M p (peak molecular weight) in the range of 550 g / mol to 1,677,000 g / mol.
[0105] Differential Scanning Calorimetry (DSC): The glass transition temperature of the acrylic polymer was measured during the second heating using a TA Instruments Q2000DSC in N2 at a heating rate of 10°C / min. The first heating was used to heat the sample to 170°C at a heating rate of 10°C / min, and then the sample was cooled to 0°C at a cooling rate of 10°C / min. The sample weight was controlled at 5-10 mg.
[0106] Thermogravimetric analysis (TGA): The thermal decomposition temperature of acrylic polymer was measured using TA Instruments Q5000 TGA in N2 at a heating rate of 10°C / min. The sample weight was controlled at 5-10 mg. The sample was pre-dried in a vacuum oven at 100°C overnight.
[0107] Total light transmittance : Total light transmittance was measured from film and / or plaque samples in transmission mode using a Perkin Elmer Lambda 950 with a 150 mm integrating sphere. The selected UV / Vis wavelength range was 200 nm to 800 nm in the UV / Vis region.
[0108] Haze : Optical haze of transparent film and / or plaque samples was measured using BYK HazeGard Plus according to ASTM method D1003.
[0109] Tensile strength and elongation: After 23°C / 48 hours preconditioning, tensile strength, modulus and elongation of tensile bars were evaluated using ASTM D638 method using Instron Model 4202 at a crosshead speed of 5 mm / min. The tensile length was 6" and the width was 0.50". The sample thickness was 0.125".
[0110] Refractive Index : The refractive index of the polymer film was measured at three different wavelengths of 402 nm, 518 nm and 636.5 nm using an optical prism coupler Metricon 2010 from Metricon Inc., while the refractive index was calculated at a selected wavelength of 589 nm.
[0111] NMR : Prepare for NMR by dissolving approximately 200 mg of the pellet in approximately 4 ml of CDCl3 in a separate 10 mm NMR tube. 13 C NMR of samples. 1 H spectra before and after derivatization of MAA were obtained on a Bruker AVIII HD 500 (11.07T) spectrometer using a 5 mm 1 H / 19 F / 13 C TXO probe acquired at 25°C. Acquired at 50°C using a 10 mm BBO probe on a Bruker AV 400 (9.4T) 13 C spectrum.
[0112] Vicat softening temperature : Samples were tested in an Instron HV6M using ASTM method D1525 at 10 N and 50 N forces. Sample heating rate was controlled at a rate of 50 °C / hour. Injection molded samples were annealed at about 20 °C below Tg for 16 hours and stored in a drying oven before testing.
[0113] Water absorption : Injection molded samples were immersed in a DI water bath (23°C) using ASTM method D570. Water absorption values were measured based on the weight increase when the sample surface was cleaned with a dry paper towel.
[0114] Notched Izod impact : Notched Izod impact strength or impact resistance is measured using ASTM D256 method using a 1.0J impact hammer at 23°C / 50% relative humidity. The Izod notched bar is injection molded with dimensions of 10.2 mm (width) x 100 mm (length) x 3.2 mm (thickness).
[0115] Syndiotacticity :use 13The syndiotacticity (rr) of the solution polymerized pMMA copolymer was about 60% as determined by C NMR from the chemical shift of 44.5 ppm. 13 The isotacticity (mm) and atacticity (rm) measured by CNMR from 45.5 ppm and 45.0 ppm were about 4% and about 36%, respectively. 13 C NMR stereoregularity calculations were performed using C α The carbon signal is completed.
[0116] Example 1 (pMMA copolymer containing 1.9% tert-butyl cyclohexyl methacrylate, Tg of 127°C)
[0117] This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and tert-butylcyclohexyl methacrylate (from Sartomer, melting temperature of 43°C). 88.07 parts of methyl methacrylate and 1.93 parts of tert-butylcyclohexyl methacrylate (solid, dissolved in 10 parts of methyl methacrylate) were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 380 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.247 parts. The polymerization reaction occurred at 66°C for 7 hours. When the conversion reached >60%, the residual monomer was removed by methanol precipitation (MeOH, at least ×10 times). After the sample was dried at 160°C overnight, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least ×10 times). The reprecipitated white powder sample was dried at 120°C overnight and dried in a vacuum oven at 165°C for 8 hours. The melt flow rate of the polymer was measured at 230° C. under 3.8 kg and was 1.5 g / 10 minutes. The refractive index of the resulting polymer was measured at 589 nm and was 1.491.
[0118] use 1 H NMR confirmed that the obtained polymer had a composition of pMMA / tert-butylcyclohexyl methacrylate (98.1 / 1.9 w / w), and the ratio of trans isomer / cis isomer in the copolymer containing t-BCHMA was 94% / 6%. 13The syndiotacticity of the copolymer was measured by C NMR from the chemical shift of 44.5ppm to be 60%, while the isotacticity and atacticity were measured from 45.5ppm and 45.0ppm to be 4% and 36%. The glass transition temperature of the resulting polymer was measured to be 127°C in N2 at a heating rate of 10°C / min using DSC. The weight average molecular weight Mw of the resin was measured using GPC to be 118,000g / mol, and the Mw / Mn (polydispersity) value was 2.1. The transmittance of the 120um film was measured at 560nm using Lambda 950 to be 92.2%, and the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 0.3%.
[0119] Example 2 (pMMA copolymer containing 2.7% tert-butyl cyclohexyl methacrylate, Tg of 127°C)
[0120] This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and tert-butylcyclohexyl methacrylate (from Sartomer, melting temperature of 42°C). 87.28 parts of methyl methacrylate and 2.72 parts of tert-butylcyclohexyl methacrylate (solid, dissolved in 10 parts of methyl methacrylate) were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 380 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.211 parts. The polymerization reaction occurred at 66°C for 7 hours. When the conversion reached >60%, the residual monomer was removed by methanol precipitation (MeOH, at least ×10 times). After the sample was dried at 160°C overnight, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least ×10 times). The reprecipitated white powder sample was dried at 120°C overnight and dried in a vacuum oven at 165°C for 8 hours. The melt flow rate of the polymer was measured at 230° C. under 3.8 kg and was 1.6 g / 10 minutes. The refractive index of the resulting polymer was measured at 589 nm and was 1.491.
[0121] use 1 H NMR confirmed that the obtained polymer had a composition of pMMA / tert-butylcyclohexyl methacrylate (97.0 / 3.0 w / w), and the ratio of trans isomer / cis isomer in the copolymer containing t-BCHMA was 96% / 4%. 13The syndiotacticity of the copolymer was measured by C NMR from the chemical shift of 44.5ppm to be 60%, while the isotacticity and atacticity were measured from 45.5ppm and 45.0ppm to be 4% and 36%. The glass transition temperature of the resulting polymer was measured in N2 at a heating rate of 10℃ / min using DSC to be 127℃. The weight average molecular weight Mw of the resin was measured using GPC to be 117,000g / mol, and the Mw / Mn (polydispersity) value was 1.6. The transmittance of the 120um film was measured at 560nm using Lambda 950 to be 92.2%, and the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 0.4%.
[0122] Example 3 (pMMA copolymer containing 7.2% tert-butyl cyclohexyl methacrylate, Tg = about 129°C)
[0123] This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and tert-butylcyclohexyl methacrylate (from Sartomer, melting temperature of about 42°C). 82.55 parts of methyl methacrylate and 7.19 parts of tert-butylcyclohexyl methacrylate (solid, dissolved in 10 parts of methyl methacrylate) were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 380 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.263 parts. The polymerization reaction occurred at 67°C for 7 hours. When the conversion reached >60%, the residual monomer was removed by methanol precipitation (MeOH, at least × 10 times). After the sample was dried at 160°C overnight, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least × 10 times). The reprecipitated white powder sample was dried at 120°C overnight and dried in a vacuum oven at 165°C for 8 hours. The melt flow rate of the polymer was measured at 230° C. under 3.8 kg and was 2.9 g / 10 minutes. The refractive index of the resulting polymer was measured at 589 nm and was 1.489.
[0124] use 1 H NMR confirmed that the obtained polymer had a composition of pMMA / tert-butylcyclohexyl methacrylate (92.4 / 7.6 w / w), and the ratio of trans isomer / cis isomer in the copolymer containing t-BCHMA was 86% / 14%. 13The syndiotacticity of the copolymer was measured by C NMR from the chemical shift of 44.5ppm to be 61%, while the isotacticity and atacticity were measured from 45.5ppm and 45.0ppm to be 3% and 36%. The glass transition temperature of the resulting polymer was measured in N2 at a heating rate of 10℃ / min using DSC to be 129℃. The weight average molecular weight Mw of the resin was measured using GPC to be 96,000g / mol, and the Mw / Mn (polydispersity) value was 1.6. The transmittance of the 120um film was measured at 560nm using Lambda 950 to be 92.2%, and the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 0.3%.
[0125] Example 4 (pMMA copolymer containing 9.8% tert-butyl cyclohexyl methacrylate, Tg = about 132°C)
[0126] This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and tert-butylcyclohexyl methacrylate (from Sartomer, melting temperature of 43°C). 79.85 parts of methyl methacrylate and 9.89 parts of tert-butylcyclohexyl methacrylate (solid, dissolved in 10 parts of methyl methacrylate) were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 360 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.265 parts. The polymerization reaction occurred at 68°C for 7 hours. When the conversion reached >60%, the residual monomer was removed by methanol precipitation (MeOH, at least ×10 times). After the sample was dried at 160°C overnight, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least ×10 times). The reprecipitated white powder sample was dried at 120°C overnight and dried in a vacuum oven at 165°C for 8 hours. The melt flow rate of the polymer was measured at 230° C. under 3.8 kg and was 7.5 g / 10 minutes. The refractive index of the resulting polymer was measured at 589 nm and was 1.488.
[0127] use 1 H NMR confirmed that the obtained polymer had a composition of pMMA / t-BCHMA (90.2 / 9.8 w / w), and the ratio of trans isomer / cis isomer in the copolymer containing t-BCHMA was 96% / 4%. 13The syndiotacticity of the copolymer was measured by C NMR from the chemical shift of 44.5ppm to be 61%, while the isotacticity and atacticity were measured from 45.5ppm and 45.0ppm to be 3% and 36%. The glass transition temperature of the resulting polymer was measured in N2 at a heating rate of 10℃ / min using DSC to be 132℃. The weight average molecular weight Mw of the resin was measured using GPC to be 80,000g / mol, and the Mw / Mn (polydispersity) value was 1.6. The transmittance of the 120um film was measured at 560nm using Lambda 950 to be 92.3%, and the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 0.3%.
[0128] Example 5 (pMMA terpolymer containing 2.0% tert-butyl cyclohexyl methacrylate and 4.3% MAA, Tg = about 136°C)
[0129] This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and tert-butylcyclohexyl methacrylate (from Sartomer, melting temperature 43°C). 83.70 parts of methyl methacrylate, 4.34 parts of methacrylic acid and 1.96 parts of tert-butylcyclohexyl methacrylate (solid, dissolved in 10 parts of methyl methacrylate) were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 390 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.285 parts. The polymerization reaction occurred at 68°C for 7 hours. When the conversion reached >60%, the residual monomer was removed by methanol precipitation (MeOH, at least ×10 times). After the sample was dried at 160°C overnight, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least ×10 times). The reprecipitated white powder sample was dried at 120°C overnight and dried in a vacuum oven at 165°C for 8 hours. The melt flow rate of the polymer measured at 230° C. under 3.8 kg was 0.7 g / 10 minutes. The refractive index of the resulting polymer measured at 589 nm was 1.492.
[0130] use 1 H NMR and 13 C NMR confirmed that the obtained polymer had a composition of pMMA / t-BCHMA / MAA / acid anhydride (93.5 / 2.0 / 4.1 / 0.4 w / w / w), and the ratio of trans isomer / cis isomer in the copolymer containing t-BCHMA was 98% / 2%. 13CNMR measured the syndiotacticity of the copolymer from the chemical shift of 44.5ppm as 61%, while the isotacticity and atacticity were 3% and 36% from 45.5ppm and 45.0ppm. The glass transition temperature of the resulting polymer was 136°C measured in N2 at a heating rate of 10°C / min using DSC. The weight average molecular weight Mw of the resin was 130,000g / mol using GPC, and the Mw / Mn (polydispersity) value was 1.7. The transmittance of the 120um film was measured at 560nm using Lambda 950 as 92.3%, and the haze was 0.3% using a haze meter (Haze Gard Plus from BYK).
[0131] Example 6 (pMMA copolymer containing 1.2% 3,3,5-trimethylcyclohexyl methacrylate, Tg of 126°C)
[0132] This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and 3,3,5-trimethylcyclohexyl methacrylate (TMCHMA, from Sartomer). 98.83 parts of methyl methacrylate and 1.17 parts of 3,3,5-trimethylcyclohexyl methacrylate were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 380 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.320 parts. The polymerization reaction occurred at 70°C for 7 hours. When the conversion reached >60%, the residual monomer was removed by methanol precipitation (MeOH, at least × 10 times). After the sample was dried at 160°C overnight, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least × 10 times). The reprecipitated white powder sample was dried at 120°C overnight and dried in a vacuum oven at 170°C for 8 hours. The melt flow rate of the polymer was measured at 230° C. under 3.8 kg and was 6.3 g / 10 minutes. The refractive index of the obtained polymer was measured at 589 nm and was 1.491.
[0133] use 1 H NMR confirmed that the obtained polymer had a composition of pMMA / 3,3,5-trimethylcyclohexyl methacrylate (98.7 / 1.3 w / w), and the ratio of trans isomer / cis isomer in the copolymer containing t-TMCHMA was 87% / 13%. 13The syndiotacticity of the copolymer was measured by C NMR from the chemical shift of 44.5ppm to be 60%, while the isotacticity and atacticity were measured from 45.5ppm and 45.0ppm to be 4% and 36%. The glass transition temperature of the resulting polymer was measured in N2 at a heating rate of 10℃ / min using DSC to be 126℃. The weight average molecular weight Mw of the resin was measured using GPC to be 80,000g / mol, and the Mw / Mn (polydispersity) value was 1.7. The transmittance of the 120um film was measured at 560nm using Lambda 950 to be 92.2%, and the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 0.3%.
[0134] Example 7 (pMMA copolymer containing 2% 3,3,5-trimethylcyclohexyl methacrylate, Tg of 126°C)
[0135] This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and 3,3,5-trimethylcyclohexyl methacrylate (TMCHMA, from Sartomer). 97.99 parts of methyl methacrylate and 2.01 parts of 3,3,5-trimethylcyclohexyl methacrylate were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 380 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.207 parts. The polymerization reaction occurred at 70°C for 7 hours. When the conversion reached >60%, the residual monomer was removed by methanol precipitation (MeOH, at least × 10 times). After the sample was dried at 160°C overnight, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least × 10 times). The reprecipitated white powder sample was dried at 120°C overnight and dried in a vacuum oven at 170°C for 8 hours. The melt flow rate of the polymer was measured at 230°C under 3.8 kg. 1.2 The refractive index of the obtained polymer measured at 589 nm was 1.491.
[0136] use 1 H NMR confirmed that the obtained polymer had a composition of pMMA / 3,3,5-trimethylcyclohexyl methacrylate (98.1 / 1.9 w / w), and the ratio of trans isomer / cis isomer in the copolymer containing t-TMCHMA was 87% / 13%. 13The syndiotacticity of the copolymer was 60% as measured by C NMR from the chemical shift of 44.5 ppm, while the isotacticity and atacticity were 4% and 36% at 45.5 ppm and 45.0 ppm, respectively. The glass transition temperature of the obtained polymer was 200 °C / min in N2 using DSC at a heating rate of 10 °C / min. 126℃ The weight average molecular weight Mw of the resin was measured using GPC to be 124,000 g / mol, and the Mw / Mn (polydispersity) value was 1.7. The transmittance of the 120 um film was measured at 560 nm using a Lambda 950 to be 92.2%, and the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 0.5%.
[0137] Example 8 (pMMA copolymer containing 2.6% tert-butyl cyclohexyl methacrylate + 1% 3,3,5-trimethylcyclohexyl methacrylate, Tg is 128°C)
[0138] This example demonstrates the preparation of a high molecular weight terpolymer of methyl methacrylate, tert-butylcyclohexyl methacrylate (from Sartomer, melting temperature 43°C) and 3,3,5-trimethylcyclohexyl methacrylate (from Sartomer). 86.29 parts of methyl methacrylate, 2.55 parts of tert-butylcyclohexyl methacrylate (solid, dissolved in 10 parts of methyl methacrylate) and 0.97 parts of 3,3,5-trimethylcyclohexyl methacrylate were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 320 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.192 parts. The polymerization reaction occurred at 69°C for 7 hours. When the conversion reached >60%, the residual monomers were removed by methanol precipitation (MeOH, at least ×10 times). After drying the sample at 160°C overnight, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least × 10 times). The reprecipitated white powder sample was dried at 120°C overnight and dried in a vacuum oven at 175°C for 8 hours. The melt flow rate of the polymer was measured at 230°C under 3.8 kg to be 1.6 g / 10 minutes. The refractive index of the resulting polymer was measured at 589 nm to be 1.491.
[0139] For the relevant terpolymers, use 1H NMR confirmed that the obtained polymer had a composition of pMMA / tert-butylcyclohexyl methacrylate / 3,3,5-trimethylcyclohexyl methacrylate (96.4 / 2.6 / 1.0 w / w), a trans isomer / cis isomer ratio of 90% / 10% in t-BCHMA, and a trans isomer / cis isomer ratio of 87% / 13% in TMCHMA. 13 The syndiotacticity of the copolymer was measured by C NMR from the chemical shift of 44.5ppm to be 60%, while the isotacticity and atacticity were measured from 45.5ppm and 45.0ppm to be 4% and 36%. The glass transition temperature of the resulting polymer was measured to be 128°C in N2 at a heating rate of 10°C / min using DSC. The weight average molecular weight Mw of the resin was measured using GPC to be 116,000g / mol, and the Mw / Mn (polydispersity) value was 1.8. The transmittance of the 120um film was measured at 560nm using Lambda 950 to be 92.2%, and the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 0.3%.
[0140] Example 9 (pMMA copolymer containing 6.1% tert-butyl cyclohexyl methacrylate + 1% 3,3,5-trimethylcyclohexyl methacrylate, Tg is 128°C)
[0141] This example demonstrates the preparation of a high molecular weight terpolymer of methyl methacrylate, tert-butylcyclohexyl methacrylate (from Sartomer, melting temperature 43°C) and 3,3,5-trimethylcyclohexyl methacrylate (from Sartomer). 86.29 parts of methyl methacrylate, 2.55 parts of tert-butylcyclohexyl methacrylate (solid, dissolved in 10 parts of methyl methacrylate) and 0.97 parts of 3,3,5-trimethylcyclohexyl methacrylate were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 320 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.192 parts. The polymerization reaction occurred at 69°C for 7 hours. When the conversion reached >60%, the residual monomers were removed by methanol precipitation (MeOH, at least ×10 times). After drying the sample at 160°C overnight, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least 10 times). The reprecipitated white powder sample was dried at 120°C overnight and dried in a vacuum oven at 175°C for 8 hours. The melt flow rate of the polymer was measured at 230°C under 3.8 kg to be 1.8 g / 10 minutes. The refractive index of the resulting polymer was measured at 589 nm to be 1.489.
[0142] For the relevant terpolymers, use1 H NMR confirmed that the obtained polymer had a composition of pMMA / tert-butylcyclohexyl methacrylate / 3,3,5-trimethylcyclohexyl methacrylate (92.9 / 6.1 / 1.0 w / w), a trans isomer / cis isomer ratio of 93% / 7% in t-BCHMA, and a trans isomer / cis isomer ratio of 87% / 13% in TMCHMA. 13 The syndiotacticity of the copolymer was measured by C NMR from the chemical shift of 44.5ppm to be 60%, while the isotacticity and atacticity were measured from 45.5ppm and 45.0ppm to be 4% and 36%. The glass transition temperature of the resulting polymer was measured to be 128°C in N2 at a heating rate of 10°C / min using DSC. The weight average molecular weight Mw of the resin was measured using GPC to be 107,000g / mol, and the Mw / Mn (polydispersity) value was 1.8. The transmittance of the 120um film was measured at 560nm using Lambda 950 to be 92.2%, and the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 0.3%.
[0143] Example 10 (pMMA copolymer containing 1.6% 3,3,5-trimethylcyclohexyl methacrylate + 3.1% MMA, Tg is 132°C)
[0144] This example demonstrates the preparation of a high molecular weight terpolymer of methyl methacrylate, 3,3,5-trimethylcyclohexyl methacrylate (CD421, from Sartomer) and methacrylic acid (MMA). 95.42 parts of methyl methacrylate, 3.05 parts of methacrylic acid and 1.63 parts of 3,3,5-trimethylcyclohexyl methacrylate were added to a reaction vessel containing 300 parts of toluene and reacted at a temperature close to 23°C with a mechanical stirring speed of 360 rpm. In addition, AIBN (from Aldrich) was used as an initiator in an amount of 0.269 parts. The polymerization reaction occurred at 68°C for 7 hours. When the conversion reached >60%, the residual monomer was removed by methanol precipitation (MeOH, at least ×10 times). After the sample was dried overnight at 160°C, the resulting polymer was redissolved in acetone and reprecipitated in MeOH (at least ×10 times). A sample of the reprecipitated white powder was dried overnight at 120°C and in a vacuum oven at 175°C for 8 hours. The melt flow rate of the polymer was measured at 230°C under 3.8 kg to be 1.1 g / 10 minutes. The refractive index of the resulting polymer was measured at 589 nm to be 1.492.
[0145] use 1 H NMR and 13C NMR confirmed that the obtained polymer had a composition of pMMA / 3,3,5-trimethylcyclohexyl methacrylate / MAA / anhydride (95.3 / 1.6 / 2.6 / 0.5 w / w), and the ratio of trans isomer / cis isomer in the copolymer containing TMCHMA was 87% / 13%. 13 C NMR measured the syndiotacticity of the copolymer from the chemical shift of 44.5ppm to be 60%, while the isotacticity and atacticity were 4% and 36% from 45.5ppm and 45.0ppm. The glass transition temperature of the obtained polymer was measured to be 132°C in N2 at a heating rate of 10°C / min using DSC. The weight average molecular weight Mw of the resin was measured to be 102,000g / mol using GPC, and the Mw / Mn (polydispersity) value was 1.7. The transmittance of the 120um film was measured to be 92.2% at 560nm using Lambda950, and the haze was measured to be 0.3% using a haze meter (Haze Gard Plus from BYK).
[0146] Example 11 (1% tert-butyl cyclohexyl methacrylate, Tg = 119°C)
[0147] This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and tert-butyl cyclohexyl methacrylate (from Sartomer, melting temperature 43°C). 9816 parts of methyl methacrylate and 150 parts of tert-butyl cyclohexyl methacrylate were added to a reaction vessel and reacted at approximately 0°C under N2 with a mechanical stirring speed of 100 rpm. In addition, 1.6 parts of 531 (from Arkema) was used as an initiator, while 32 parts of n-dodecyl mercaptan (n-DDM, from Aldrich) was used as a chain transfer agent, and 1.0 parts of di-tert-dodecyl disulfide (DtDDS, from Arkema) was used. The polymerization reaction occurred at 160°C for 5 hours. When the conversion rate reached 50%, the residual monomers were removed by the exhaust system. The resulting polymer was passed through a single screw extruder at a mold temperature of 235°C and a barrel temperature of 230°C-245°C. The melt stream passed through a water bath before pelletizing. The polymer was then pelletized into 3-4 mm long resin pellets and dried in a drying oven at 100°C for 8 hours. The melt flow rate of the polymer was measured at 230°C at 3.8 kg to be 2.1 g / 10 minutes. The refractive index of the resulting polymer was measured at 589 nm to be 1.491.
[0148] use 1H NMR confirmed that the resulting polymer had a composition of pMMA / tert-butylcyclohexyl methacrylate (98.5 / 1.5 w / w), with a trans / cis isomer ratio of 86% / 14% in t-BCHMA. The syndiotacticity of the copolymer was measured to be 51% from a chemical shift of 44.5 ppm using 13C NMR, while the isotacticity and atacticity were 8% and 41% from 45.5 ppm and 45.0 ppm, respectively. The glass transition temperature of the resin measured using DSC at a heating rate of 10°C / min in N2 was 119°C, while the Vicat temperature detected at 10N was 118°C. The weight average molecular weight Mw of the resin was measured using GPC to be 105,000 g / mol, and the Mw / Mn (polydispersity) value was 2.0. The light transmittance of the 3.2 mm plaque was measured at 560 nm using a Lambda 950 to be 92.3%, while the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 0.5%. The tensile modulus of the test sample was 3.1 GPa, the tensile strength was 72 MPa, and the tensile elongation was 10%.
[0149] Example 12 (Copolymer of Example 11 containing 35% impact modifier, Tg = about 118°C).
[0150] This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and tert-butyl cyclohexyl methacrylate (containing 86% trans isomer / 14% cis isomer) (melt flow rate 2.2 g / 10 min at 230°C) and a commercial core-shell acrylic impact modifier (35% MPD85T from Altuglas).
[0151] A high Tg hydrophobic acrylic resin (Tg = 119°C) was compounded with a core-shell acrylic impact modifier (MPD85T from Altuglas) having an average particle size of about 250 nm and formed into an impact acrylic resin using a twin screw extruder (from Leistritz) at a compounding speed of 50 lbs / hr and a die temperature of 230°C under full vacuum. UV stabilizers were also added to the formulation by pre-blending during compounding. The compounded acrylic pellets were cut through a water cooling bath at ambient temperature and dried at 100°C.
[0152]
[0153] The melt flow rate of the obtained polymer was measured at 230°C under 3.8kg to be 0.72g / 10min. The refractive index of the obtained polymer was measured at 589nm to be 1.491. The glass transition temperature of the resin measured by DSC at a heating rate of 10°C / min in N2 was 118°C, and the Vicat softening temperature detected at 10N was 117°C. The weight average molecular weight Mw of the resin was measured using GPC to be 104,000g / mol, and the Mw / Mn (polydispersity) value was 1.9. The transmittance of the 180um film was measured at 560nm using Lambda 950 to be 91.6%, and the haze was measured using a haze meter (Haze Gard Plus from BYK) to be 2.0%. The tensile modulus of the test sample was 2.0GPa, the tensile strength was 47MPa, and the tensile elongation was 75%. The weight increase percentage of water absorption measured after immersion in water for 504 hours was 1.45%. The measured notched cantilever beam impact strength is 4.8 kJ / m 2 .
[0154] Table 1: Composition and physical properties
[0155]
[0156] Table 2: Composition and physical properties (continued)
[0157]
[0158] Table 3: Composition and physical properties (continued)
[0159]
[0160]
[0161] The results summarized in Tables 1-3 show that incorporating up to 20 wt% of at least one of tert-butylcyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate into an acrylic copolymer, such that at least 80 wt% of the comonomer is the trans isomer, can provide improvements in physical properties. As can be seen from the table, the improved properties are: a haze value of less than 2.5%, a light transmittance value of at least 91% through a 120 μm film at a wavelength of 560 nm; a refractive index of 1.47 to 1.50 at a wavelength of 589 nm; and a water absorption of less than 2 wt% after being placed in water at 60°C for at least 504 hours.
Claims
1. An acrylic copolymer comprising as a polymerizable monomer: a) 0.2 to 20 wt% of monomer units comprising at least one of tert-butylcyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, or a mixture thereof; wherein the monomer a) comprises at least 80 wt% of the trans isomer; b) 80% to 99.8% by weight of (meth)acrylate monomer units; The acrylic copolymer has: i) a Tg of 116°C to 145°C, preferably 120°C to 145°C, more preferably 125°C to 145°C and most preferably 125°C to 140°C; and ii) a weight average molecular weight (Mw) of at least 65,000 g / mol, preferably at least 75,000 g / mol, and more preferably at least 90,000 g / mol and most preferably at least 100,000 g / mol.
2. The acrylic copolymer according to claim 1, wherein the acrylic copolymer has: iii) a syndiotacticity (rr) of at least 50%.
3. The acrylic copolymer according to claim 1, wherein the acrylic copolymer has the following characteristics: iv) haze value is less than 2.5%; v) a light transmittance value through a 120 μm film at a wavelength of 560 nm of at least 91%; vi) a refractive index of 1.47 to 1.50 at a wavelength of 589 nm; and vii) The water absorption after being placed in water at 60°C for at least 504 hours is less than 2% by weight.
4. The acrylic copolymer of claim 1, wherein the copolymer comprises at least 51% by weight of methyl methacrylate monomer units.
5. The acrylic copolymer according to claim 1, further comprising as a polymerizable monomer: c) 0.01% to 49.9% by weight of at least one additional monomer copolymerizable with monomer a) and monomer b).
6. The acrylic copolymer of claim 5, wherein the additional monomer c) comprises at least one of methacrylic acid, acrylic acid, itaconic acid, α-methylstyrene, maleic anhydride, maleimide, isobornyl methacrylate, norbornyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, tetrahydrofuranyl methacrylate, acrylamide and methacrylamide, or a mixture thereof.
7. The acrylic copolymer of claim 5, wherein the monomer c) is present in the form of 0.01 wt% to 25 wt% of polymerized monomer based on the weight of the acrylic copolymer.
8. A composition comprising the acrylic copolymer according to claim 1.
9. The composition of claim 8, comprising 100 ppm to 2000 ppm by weight of an antioxidant, wherein the antioxidant comprises at least one of hydroxyphenylbenzotriazole, a sterically hindered phenolic compound, an organic phosphite, a hindered amine, and a combination thereof.
10. The composition of claim 8, comprising 5 to 60 weight percent of an impact modifier, based on the total weight of the composition.
11. The composition of claim 10, wherein the impact modifier comprises at least one of a core-shell impact modifier, an acrylic block copolymer, a self-assembled nanostructured polymer, or any combination thereof.
12. The composition of claim 10, wherein the impact modifier comprises a core-shell impact modifier.
13. The composition of claim 8, comprising at least one of poly(methyl methacrylate) / ethyl acrylate copolymer; poly(methyl methacrylate) / methyl acrylate copolymer; poly(methyl methacrylate) / methacrylate copolymer; poly(styrene acrylonitrile, SAN); polyvinylidene fluoride; a copolymer of vinylidene fluoride and hexafluoropropylene; polylactic acid; or a combination thereof.
14. The composition of claim 8, wherein the composition comprises an effective amount of one or more additives, the additive comprising at least one of an impact modifier, a filler, a surface modification additive, a processing aid, a fiber, a lubricant, a matting agent, a heat stabilizer, a flame retardant, a synergist, a pigment, or a colorant.
15. The composition of claim 8, wherein the composition has the following characteristics: iv) haze value is less than 2.5%; v) a light transmittance value through a 120 μm film at a wavelength of 560 nm of at least 91%; vi) a refractive index of 1.47 to 1.50 at a wavelength of 589 nm; and vii) The water absorption after being placed in water at 60°C for at least 504 hours is less than 2% by weight.
16. The composition of claim 8, wherein a 3.2 mm thick sample of the composition has no visible stress cracks or cracking defects after exposure to 75 cycles of -40°C to 80°C / 85% RH for 600 hours.
17. An article comprising the acrylic copolymer of claim 1, wherein the article is at least one of an automotive front interior thick lens, an automotive interior thin lens, a smart phone, an imaging lens, a photovoltaic cell, a high heat LED diffuser sheet / film, a digital print on a hydrophobic surface, a (window) profile, a surface protection application, an automotive thin-walled part, a medical device, a lithium-ion battery adhesive electronic component, an optically thin polarizer for LED / OLED displays, a laptop computer, and an electronic component in a solar electronic device.
18. An article comprising the composition of claim 8, wherein the article is at least one of an automotive front interior thick lens, an automotive interior thin lens, a smart phone, an imaging lens, a photovoltaic cell, a high heat LED diffuser sheet / film, a digital print on a hydrophobic surface, a (window) profile, a surface protection application, an automotive thin-walled part, a medical device, a lithium-ion battery adhesive, an electronic component, an optically thin polarizer for an LED / OLED display, a laptop computer, and an electronic component in a solar electronic device.
Citation Information
Patent Citations
High temperature acrylic sheet
US10043930B2
Method of preparation of a composition comprising a copolymer of methyl methacrylate and methacrylic acid
US20180362688A1